The Sedimentary Record of Deglaciation in the Western Himalaya recorded in the Indus Delta, Pakistan - Cliff, PD; Giosan, L; Campbell, IH; Blusztajn, J; Pringle, M; Tabrez, AR; Alizai, A; Rabbani, MM; Vanlaniningham, S (Himalayan Journal of Sciences, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> DOI = 10.3126/hjs.v5i7.1246 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.41